The complete chloroplast genome of Pseudognaphalium affine (D.Don) Anderb. (Asteraceae). Issue 11 (2nd November 2021) - Xie, Li; Zhao, Jiale; Liu, Rong
Abstract: Pseudognaphalium affine (D.Don) Anderb. is an annual herbaceous plant used as a vegetable and traditional medicine. Here, we sequenced and assembled the complete chloroplast genome of P. affine . The plastome is 151, 573 bp in size with a pair of inverted repeat regions (IRs) of 24, 849 bp each, a large single-copy region (LSC) of 83, 632 bp, and a small single-copy region (SSC) of 18, 243 bp. The overall GC content of the whole plastome is 37.33%, and the IR regions are more GC rich (43.08%) than the LSC (35.30%) and SSC (31.03%) regions. It contains 129 genes, including 83 protein-coding genes, 36 tRNAs, eight rRNAs, and two pseudogenes. Phylogenetic analysis showed that P. affine is most closely related to Leontopodium leiolepis . This genome will provide a useful genetic resource for future conservation, evolution, and phylogeny studies of P. affine and the tribe Inuleae.